Resilience as a Form of Contestation in Langston Hughes' Early Poetry - Fernández Alonso, Alba; Barros del Río, María Amor (Miscelánea: A Journal of English and American Studies, 2019)
The history of the African American community has been inexorably bound to the concepts of oppression, downgrading, racism, hatred and trauma. Although the association between racism and concomitant negative psychological outcome has been widely assessed, little work has been done to study the role of literature as a cultural means to promote resilience among this oppressed group. Langston Hughes (1902-1967) stands out as a novelist, poet and playwright, and is one of the primary contributors to the Harlem Renaissance movement. Following the framework of theories of resilience, this article analyses the representation of adversity and positive adaptation in Langston Hughes’s early stage poetry, and assesses his contribution to resilience among the African American people at a time of hardship and oppression.
Keywords: Langston Hughes; African American poetry; Harlem Renaissance; trauma; resilience